Maternal attitudes to newborn screening for fragile X syndrome1. Issue 2 (9th January 2013) - Christie, Louise; Wotton, Tiffany; Bennetts, Bruce; Wiley, Veronica; Wilcken, Bridget; Rogers, Carolyn; Boyle, Jackie; Turner, Catherine; Hansen, Jessica; Hunter, Matthew; Goel, Himanshu; Field, Michael
Abstract Although fragile X syndrome (FXS) is the commonest cause of inherited intellectual disability the mean age of diagnosis in Australia is 5.5 years. Newborn screening for FXS can provide an early diagnosis, preventing the "diagnostic odyssey", allowing access to early interventions, and providing reproductive information for parents. Parents of affected children support newborn screening, but few clinical studies have evaluated community attitudes. A pilot study in 2009–2010 was performed in a tertiary hospital to explore feasibility and maternal attitudes. FXS testing of male and female newborns was offered to mothers in addition to routine newborn screening. Mothers were provided with information about FXS, inheritance pattern, carrier status, and associated adult‐onset disorders. One thousand nine hundred seventy‐one of 2, 094 mothers (94%) consented to testing of 2, 000 newborns. 86% completed the attitudinal survey and 10% provided written comments. Almost all parents (99%) elected to be informed of both premutation and full mutation status and there was little concern about identification of carrier status or associated adult‐onset disorders. Most mothers (96%) were comfortable being approached in the postnatal period and supported testing because no extra blood test was required. Mothers considered an early diagnosis beneficial to help prepare for a child with additional needs (93%) and for reproductive planning (64%). Some were anxious about the potential test results (10%) and others felt their feelings towards their newborn may change if diagnosed with FXS (16%). High participation rates and maternal attitudes indicate a high level of maternal acceptance and voluntary support for newborn screening for FXS. © 2013 Wiley Periodicals, Inc.